Corporate social responsibility in supply chains of small and medium-sized enterprises - Lee, Hee-Yong; Kwak, Dong-Wook; Park, Jeong-Yang (Wiley, 2017)
Research has shown that implementation of corporate social responsibility (CSR) practice represents a considerable challenge for small and medium-sized enterprises (SMEs). This research conceptualises the dimensions and contingencies of CSR in SMEs’ supply chains. Drawing on institutional theory and stakeholder theory, we investigates the degree of importance and implementation of CSR practices in SMEs. A large-scale questionnaire survey with SMEs in manufacturing sectors and panel discussions were conducted in South Korea. The findings indicate that SMEs tend to focus on explicit CSR practices that can be easily identified by their customers. Consistent with this, stakeholder and institutional pressures were valid in the performance of CSR practices, but largely biased to customers, government and regulatory pressures. Based on institutional theory and stakeholder theory as overarching theoretical lenses, this research contributes to offer a fuller understanding of dimensions of CSR practices in the supply chains from a SME perspective.